El gasto público en la dinámica económica de las provincias del Ecuador, 2000 - 2017. - Nancy Marina, Ramos Villa (2020)
One of Ecuador's challenges is to present more significant economic growth not only based on the influence of public spending, but also on the increase in the stock of knowledge that generates higher economic dynamics of the provinces of Ecuador in the period 2000-2017. The projections are made through the application of the Autoregressive Vectors model, taking into account as variables public spending, illiteracy and the economically active population, in their analysis a statistical study favors knowing the behavior of the variables in the period mentioned above. The results of the model show that there is a favorable relationship in the short term between public spending and economic growth so that state intervention in the economy of the provinces is justified. The research contains the following sections: the introduction in the first, second and third section, the study basis of the problem, and the respective objectives are exposed. The fourth section contains state of the art, which objectively includes the background and theoretical basis of the research work. In contrast, the fifth section pieces of evidences the applied methodology conduces the research work with their respective results. And finally in the sixth section contains the conclusions and recommendations.